Zoogeography of Termite Genus Odontotermes Holmgren in the Indian Region (Isoptera : Termitidae : Macrotermitinae) - Thakur, M. L. (Indian Forester, 1976)
Zoogeographical distribution of various species of geuus Odontotermes is discussed in the light of recent taxonomic studies by the author (unpublished). Odontotermes fear earlier reported as widely distributed throughout India is now considered restricted to Eastern zone only. Materials from the rest of the localities in India belong to a new species, O. indicus, O. horni is restricted to Ceylon and Peninsular India only. Its earlier records from Eastern zone are based on wrong identification. Similarly earlier records of O. malabaricus from some localities in Punjab and Uttar Pradesh and O. wallonensis in Uttar Pradesh are errorneous. O. malabarcius does not occur north of 20Â°lat. Record or O. taprobanes from Orissa is wrong This species is restricted to Ceylon in the Indian Region.